Semiotic Analysis of Gender Identity Transformation in the Film ‘The Danish Girl’ - Apriliani, Milah; Afifah, Wiwiek (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
The transgender phenomenon is not exclusively a post-2000s issue; historical evidence traces its presence as far back as themid-1920s. The Danish Girl (2015), directed by Tom Hooper, presents a compelling cinematic portrayal of identitytransformation, following the journey of Einar Wegener as he transitions into Lili Elbe. This study aims to analyze therepresentation of gender transition through a semiotic lens andthe pedagogical potential for English language teaching andlearning. By employing a qualitative descriptive methodology, selected scenes from the film are examined to uncover the layersof meaning that construct and communicate transgender identityby using John Fiske’s three-tiered framework of reality, representation, and ideology. By linking the analysis to Butler'sview that gender is fluid, this study demonstrates that The Danish Girl presents an exemplary understanding of thecomplex dynamics of gender identity within individuals (Inayah & Fauzi, 2024). The findings revealed: (1) The Danish Girldepicts Einar Wegener’s transition into Lili Elbe throughemotionally charged scenes and visual elements, such as costume and gesture, which signify internal conflict and identityshifts. The film constructs gender transformation usingcinematographic techniques like lighting, framing, andsymbolism while promoting individual freedom, and gender identity. (2) This film is valuable used as resource for analyzingpsychological changes and for linguistic teaching to fostercritical thinking, media literacy, and cultural awareness. By using film as authentic material, educators can createtransformative learning experiences that encourage learners toengage deeply with social issues through the English language.